The Influence of Foreign Ownership, Company Size, Profitability, and Thin Capitalization on Tax Avoidance - Mohammad Khoiru Mohamad Rusydi; Adrianus Krisna Cahyo Wibisono (University of Merdeka Malang, 2025)
This study was conducted with the aim of understanding the influence of foreign ownership, company size, profitability, and thin capitalization on tax avoidance in excise companies (cigarettes and liquors) listed on the Indonesia Stock Exchange (IDX) in the period of 2016-2020, with the total of 7 companies consisting of 5 cigarette companies and 2 liquor companies used as samples. This study was a quantitative descriptive study with the type of secondary data used was in the form of company annual reports. The data analysis technique used multiple regression analysis. The results of this study indicate that foreign ownership, company size, and thin capitalization have no effect on tax avoidance. On the other hand, profitability has an effect on tax avoidance.